A 15-Year Single-Center Experience of Endovascular Repair for Elective and Ruptured Abdominal Aortic Aneurysms. (August 2016) - Broos, Pieter P. H. L.; 't Mannetje, Yannick W.; Stokmans, Rutger A.; Houterman, Saskia; Corte, Giuseppe; Cuypers, Philippe W. M.; Teijink, Joep A. W.; van Sambeek, Marc R. H. M.
Purpose: To evaluate the differences in technical outcomes and secondary interventions between elective endovascular aneurysm repair (el-EVAR) procedures and those for ruptured aneurysms (r-EVAR).Methods: Of the 906 patients treated with primary EVAR from September 1998 until July 2012, 43 cases were excluded owing to the use of first-generation stent-grafts. Among the remaining 863 patients, 773 (89.6%) patients (mean age 72 years; 697 men) with asymptomatic or symptomatic abdominal aortic aneurysms (AAAs) were assigned to the el-EVAR group; 90 (10.4%) patients (mean age 73 years; 73 men) were assigned to the r-EVAR group based on blood outside the aortic wall on preoperative imaging. The primary study outcome was technical success; secondary endpoints, including freedom from secondary interventions and late survival, were examined with Kaplan-Meier analyses.Results: At baseline, r-EVAR patients had larger aneurysms on average (p<0.001) compared to el-EVAR patients. Technical success was comparable (p=0.052), but there were more type Ia endoleaks at completion angiography in the r-EVAR group (p=0.038). As anticipated, more patients died in the first month in the r-EVAR group (18.9% vs 2.2% el-EVAR, p<0.001). At 5 years, there was an overall survival of 65.1% for the el-EVAR patients vs 48.1% in the r-EVAR group (p<0.001). The freedom from AAA-related mortality was 95.7% for el-EVAR and 71.0% for r-EVAR (p<0.001). Five-year freedom from type I/III endoleaks was significantly lower in the r-EVAR group (78.7% vs 90.0%, p=0.003). Five-year freedom from secondary intervention estimates were not significantly different (el-EVAR 84.2% vs r-EVAR 78.2%, p=0.064).Conclusion: Within our cohort of primary EVAR patients, r-EVAR cases showed comparable stent-graft–related technical outcome. Although there was a higher incidence of type Ia endoleaks on completion angiography in the r-EVAR group, the overall secondary intervention rate was comparable to el-EVAR.